Role of Mean Platelet Volume (MPV) as a Prognostic Marker in Patients with Acute Kidney Injury - Gurvinder Singh; Satpal Aloona; Maneesh Bains; Rajneesh Bains (Wolters Kluwer Medknow Publications, 2024)
This study aimed to investigate the prognostic significance of mean platelet volume (MPV) in 50 AKI patients. Blood samples were collected according to KDIGO guidelines, and complete blood counts, including MPV, were analyzed. Significant differences in MPV were observed among patients who recovered with or without dialysis and those who expired. A statistically significant difference was present in between the mean platelet count of patients recovered without dialysis, recovered with dialysis, and the expired patients. The Area Under Curve (AUC) for MPV scores was as high as 0.842. Indicating that in up to 84% of the pairs (death-survival) the models correctly estimated that the probability of survival was higher than that of death. MPV had an optimum cutoff point of score value <9.60 with a sensitivity of 80% and specificity of 91.11%. These findings suggested that MPV could serve as a cost-effective and superior tool to creatinine in early AKI detection.